POST-GLOF RECOVERY ANALYSIS: A CASE STUDY OF THE 2019 EVENT IN GOLAIN GOL, LOWER CHITRAL, PAKISTAN - Shehla Gul; Shah Nawaz Khan; Fazli Malik; Sardar Muzaffar Hussain Zahid; Rafiq Ali Khan; Fazl-ur-Rahman (International Journal of Contemporary Issues in Social Sciences, 2024)
This study evaluates the post-disaster recovery efforts following the 2019 Glacial Lake Outburst Flood (GLOF) event in Gollain Valley, Chitral, Pakistan. A mixed-method research approach was employed, incorporating both qualitative and quantitative data collection methods. Primary data was gathered through qualitative methods, including observations and interviews, and quantitative data through questionnaires. A total of 200 questionnaires were randomly distributed, and 4 interviews were conducted. Secondary data was sourced from books, journals, the District Census Report (DCR), and online resources. The results revealed that the government played a significant role in recovery projects within the study area, with NGOs also contributing substantially. While many recovery projects have been completed, progress on others, such as road repairs in the upper regions, remains slow due to limited funding. Insufficient financial support has been provided for fully and partially damaged houses, leaving affected residents dissatisfied with stakeholders and forcing some to continue living in temporary shelters.